Blendas cimentíceas com cinzas volantes e zeólitas para cimentação de poços de petróleo : propriedades e resistência ao ataque do co2 em condições de armazenamento geológico de carbono - Ledesma, Roger Braun (2023)
This work evaluated the performance of the class G cement paste, used in cementing and plugging wells under geological carbon storage conditions, replacing part of the cement with pozzolanic materials, which were added in different amounts. The pozzolanic materials used in this work were coal fly ash from the Presidente Médici Thermoelectric Plant in Candiota, RS, and the zeolites LTA 4A synthesized from coal fly ash. The blends were prepared with 5% and 10% by weight of pozzolan materials. For the evaluation of resistance to carbonation, the samples were immersed in water saturated with CO2 at 15 MPa and 90 ° C for 7 and 14 days. The properties of the pastes were evaluated by multiple characterization techniques, such as mini-slump test, MCT, BET, pycnometry, SEM, XRD, TGA, FTIR and NMR. Single use of zeolites was detrimental to paste properties, leading to a significant loss in compressive strength, and conferred a higher volume of voids. The use of zeolites with coal fly ash in the blends led to an increase in the C-S-H main chain length and compressive strength, but still with resistance values lower than the reference paste. The carbonation depth of the blends was comparable to that of the reference paste, as well as the specific masses of the hardened pastes. In pastes and blends with coal fly ash and zeolites, the mass loss of portlandite, determined by thermogravimetric analysis, was lower than the reference paste, indicating the pozzolanic activity of these materials. The use of both zeolite and coal fly ash in replacement for cement has the main advantage of being a more sustainable material once it originated from industrial waste. Furthermore, coal fly ash is highly available, making it possible to develop pastes for oil wells to store CO2 with appropriate properties.